Integrated enhanced recovery after surgery protocol in radical cystectomy for bladder tumour—A retroprospective study - Waseem Ashraf; Arif Hamid; Sajad Ahmad Malik; Rouf Khawaja; Sajad Ahmad Para; Mohammad Saleem Wani; Saqib Mehdi (BJUI Compass)
Abstract Introduction Enhanced recovery after surgery (ERAS) is a patient‐centerd, evidence‐based approach to improve postoperative outcomes. The protocol involves multidisciplinary collaboration and standardisation of perioperative interventions. ERAS has shown positive results in reducing hospitalisation and complications. Methods The study conducted in the Department of Urology was a retro‐prospective study. It included an ERAS cohort group of 47 patients, studied prospectively from May 2021 to May 2023. These patients were compared to a historical cohort of 47 consecutive patients who underwent radical cystectomy with traditional care before the ERAS pathway was implemented. The primary outcome was hospital length of stay (LOS). Secondary outcomes included perioperative management, time to recovery milestones and complications. Results Implementation of ERAS pathway for radical cystectomy was associated with reduced hospital LOS (mean LOS 16.19 ± 2.53 days vs. 10.26 ± 3.33 days 7 days; p < 0.0001), reduced time to key recovery milestones, including days to first flatus (3.17 vs. 2.68; p = 0.013) and days to first solid food (5.19 vs. 3.45 p value < 0.0001), first stool (5.53 vs. 4.23; p < 0.0001), reductions in some complications like postoperative ileus (p value = 0.021) and need for total parental nutrition (p value = 0.023). Conclusion In conclusion, the implementation of the integrated approach facilitates a more efficient recovery process, potentially reducing healthcare costs and enhancing patient comfort.